Cohesion and Coherence in Final Project Abstracts Written by Non-English Department Undergraduate Students - Happy gusnar, Nindya Septarica; Hartono, Rudi; Suwandi, Suwandi (Universitas Negeri Semarang, 2021)
Creating text needs to be understood that it is not only about arranging the words into sentences and paragraphs but also delivering meaning. Unfortunately, not everyone can achieve good skills in writing. This study aims at analyzing the writing skills of a group of Indonesian non-English department undergraduate students. It focused on the cohesion and coherence of their production of the final project abstract. Ten texts were analyzed by employing a discourse analytical case study. Thus, it is an important matter to analyze the writing competency of students as they are at the undergraduate level, majoring in Informatics Engineering that should report their final project in English. In this study, a theory from Halliday and Matthiessen (2014) was used to analyze the cohesion while a theory from Eggins (2004), Thornburry (2005), and Paltridge and Starfield (2007) were used to analyze the coherence. An open-ended questionnaire was used to confirm the result of the analysis according to the writers’ point of view. The findings indicate that the students show a bit of weakness in achieving cohesion and coherence in creating texts due to a lack of knowledge about the theory of cohesion and coherence. The result of the study can be used as a reference and consideration in designing a suitable lesson plan for writing class.